An Evaluation Of The Factors Affecting Consumer's Perception And Behaviour Of Online Grocery Shopping In The UK - Hung, Mun Siew (2007)
The main objective of this thesis is to explore the online shopping environment as applied to the top three grocery retailers in the United Kingdom(UK) that is Tesco plc, Asda/Wal-Mart and J. Sainsbury plc.